Process The Optimizations by Taguchi Method in Drilling Machine - Prateek Singh (AG Volumes, 2021)
Material removal and surface roughness response are the primary goals of this research, which investigates and evaluates the effects of various input process parameters (cutting diameter and cutting speed) on these outcomes. Various variables have been taken into account in each experiment. The L9 Orthogonal array was used to design experiments during the milling of aluminium plate (work material). “Cutting diameter (10mm), cutting speed (1000rpm), and feed rate (0.014mm/rev)” are the most important input parameters for material removal rate and surface roughness.